Between the grammatical cause and the jurisprudential guidance - البب إبراهيم; وقاف عبد الحميد; سمعول مهران (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research deals with the grammatical cause and its relationship to the jurisprudential guidance. As it is no secret to the student in Arabic grammar that reasoning is a phenomenon characteristic of grammar, and on its basis the rulings of grammarians were established. Among those sciences; Most of the grammarians were in the field of jurisprudence, and they were fully aware of this science. Hence, this study came to show the aspects of this influence and influence between the sciences of grammar and jurisprudence, and the most important of these aspects is the explanation of grammatical rulings based on the jurisprudential judgment.